PROSpER: PReferences for the Organisation of acute health Services for oldER people: protocol for a mixed methods study. Issue 2 (30th March 2012) - Howard, Kirsten; Arendts, Glenn; Jan, Stephen; Beck, Matthew
Abstract : Background: Organisation of acute care services for people living in residential aged care facilities (RACF) is a complex area of health policy. For people living in RACF, the emergency department is often used to provide acute care; needs of RACF residents, however, are not always well met. Alternative models of delivering care must be acceptable to a variety of stakeholders; however, little is known about the values and preferences that people attach to aspects of how and where care is delivered. Methods/design: The PROSpER Study examines people's preferences for the organisation of acute healthcare services for older people in RACF. The authors aim to (1) determine which factors influence preferences of residents, carers and providers for how and where acute care is delivered and (2) determine the relative importance of these factors and the acceptable trade-offs between them. Qualitative and quantitative methods will be used. One-on-one interviews will be conducted with RACF residents, their families, staff of RACF and emergency department staff. A discrete choice study will then be designed to quantitatively assess preferences for alternative models of care delivery. Approximately 600 respondents from three respondent groups will be surveyed: older people living in RACF, family members of aged care residents and staff of RACF. A mixed logit model will be used; results will be expressed as parameter estimates (β) and odds of choosing one option over an alternative. Trade-offs between attributes will also be calculated. Ethics and dissemination: The PROSpER Study has been approved by the University of Sydney, Human Research Ethics Committee (Protocol numbers 10653 and 14382) and Royal Perth Hospital Ethics Committee (reference 2009/045). Results will be published in peer-reviewed scientific journals and via conference presentations; a newsletter will also be provided to study participants. A stakeholder roundtable will also be held to discuss the results.